2012
DOI: 10.1177/1545968312465896
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of a Repetitive Facilitative Exercise Program for the Upper Paretic Extremity After Subacute Stroke

Abstract: These findings suggest that RFE may be more effective than conventional rehabilitation in lessening impairment and improving upper-limb motor function during the subacute phase of stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 45 publications
1
38
0
Order By: Relevance
“…Despite clinical and technological advances over recent decades in the understanding and treatment of ischemic stroke, these dysfunctions significantly reduce the quality of daily life for patients [2,3,4]. However, recent rodent studies have indicated that physical exercise acts as an effective rehabilitation program for treatment of ischemic stroke [5,6] by promoting the recovery of the sensory-motor function and preventing deterioration in cognitive ability [7]. Similarly, Lee et al ., have reported that moderate activity can protect against brain injury after a stroke [8].…”
Section: Introductionmentioning
confidence: 99%
“…Despite clinical and technological advances over recent decades in the understanding and treatment of ischemic stroke, these dysfunctions significantly reduce the quality of daily life for patients [2,3,4]. However, recent rodent studies have indicated that physical exercise acts as an effective rehabilitation program for treatment of ischemic stroke [5,6] by promoting the recovery of the sensory-motor function and preventing deterioration in cognitive ability [7]. Similarly, Lee et al ., have reported that moderate activity can protect against brain injury after a stroke [8].…”
Section: Introductionmentioning
confidence: 99%
“…"Repetitive Facilitation Exercise" (RFE or Kawahira Method) is an effective rehabilitation method that can manifest the brain plasticity [5] [6] [7] [8]. However, there are problems that procedure lore of effective techniques such as RFE is difficult.…”
Section: A Need For Training Aid Device In Hemiplegic Rehabilitationmentioning
confidence: 99%
“…"Repetitive Facilitation Exercise" (RFE or Kawahira Method) is an effective rehabilitation method that can potentially manifest the brain plasticity [3][6]. This method involves inducing the stretch reflex of the human body through training, and it achieves intended movements of the patient by increasing the facilitating effect by triggering active voluntary movements.…”
Section: Introductionmentioning
confidence: 99%